Komodifikasi Produser Program X di Saluran Televisi Y - Permata Putri Pertiwi (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2023)
The purpose of this study is to examine and describe the commodification of workers experienced by the producers of Program television channel Y. This study uses a critical paradigm with a qualitative approach through observation and in-depth interviews. This study uses political economy communication, especially the commodification of labor as a theoretical framework. As one of the mass communication media, television has a purpose to make profit, where one of the biggest advantages of television is from advertising. Every program on television has a program leader or producer so the producer has a big responsibility. Television channel Y which has a special program to serve clients as advertising producers. The client as a third party then creates various pressures experienced by the producer. In addition to being responsible for internal management, the producer is also responsible for various kinds to be able to accommodate the client's wishes for the program being carried out. This study shows that producers are not aware of the commodification process they are going through. In addition, there is a transformation process for the commodification of workers which is also found in this study. Existing commodification is indicated by absolute exploitation in the form of relatively long working hours and relatively double exploitation. Producers accept exploitation as something natural because of the process of alienation, mystification, reification, and naturalization. The existing commodification is also due to the lack of human resources and the height of the client.